Nonlinear modelling of dynamic self‐heating in 28 nm bulk complementary metal–oxide semiconductor technology. Issue 7 (1st April 2015) - Sahoo, A.K.; Fregonese, S.; Scheer, P.; Celi, D.; Juge, A.; Zimmer, T.
Abstract : A new and simple approach for nonlinear modelling of the dynamic self‐heating effect in bulk complementary metal–oxide semiconductor (CMOS) field effect transistors is presented. Low‐frequency S ‐parameter measurements are performed in 28 nm bulk CMOS technology at room temperature between a 10 kHz and 3 GHz frequency range and the thermal impedance ( Z TH ) of the devices is extracted. The proposed model is validated through the measurements for different bias points. The results obtained demonstrate a reasonable agreement between theoretical prediction and experimental data.